# Thread: show me

1. ## show me

3/(x+6)=-3/4

2. -3(x+6)=4*3

3. Originally Posted by De La O 3/(x+6)=-3/4
Multiply both sides by the LCD 4(x+6)

$\displaystyle 4(x+6)\left(\frac{3}{x+6}\right)=\left(\frac{-3}{4}\right)4(x+6)$

Can you finish?

4. thanks VonNemo-you rock but as I am mathematically retarded (and prob more), can you show me the whole thing?

5. Originally Posted by De La O thanks VonNemo-you rock but as I am mathematically retarded (and prob more), can you show me the whole thing? We are all mathematically retarded in one field or another.

So, continuing from where I left off... Look at the left side of the equation, note how the $\displaystyle (x+6)s$ cancel leaving only

$\displaystyle 4\cdot3=\left(\frac{-3}{4}\right)4(x+6)$.

Now look at the right side, the fours cancel leaving

$\displaystyle 4\cdot3=-3(x+6)$.
This is why we multiplied by the LCD, to get rid of those nasty fractions.

Now, multiplying out the parentheses,

$\displaystyle 12=-3x-18$

adding 18 to both sides we get

$\displaystyle 30=-3x$

Finally, we divide each side by -3 and we are left with

$\displaystyle -10=x$ 6. 7. I would go about it by taking the reciprocal of both sides

$\displaystyle \frac{x+6}{3} = -\frac{4}{3}$

3 cancels leaving $\displaystyle x+6=-4$ which should be pretty easy solve